Traditional Snacks and Mutual Cooperation in Nyongkolan: A Study on Sasak Cultural Identity - Fitriani, Namiyah; Saidi, Abdul Gafar; Handayani, Rima Ayu; Abror, Muslih (Jurnal Al Maesarah, 2026)
This study examines the role of traditional snack production within the nyongkolan wedding tradition of the Sasak community in Lombok, focusing on its function in cultural preservation and social cohesion. The research aims to: (1) analyze the socio-cultural significance of snack-making, (2) document women’s contributions to this practice, and (3) evaluate how the banjar system supports cultural resilience. Using a qualitative phenomenological approach, data were collected through in-depth interviews with community leaders, participatory observation, and documentary analysis. Findings reveal that snack-making is a core cultural practice reinforcing social solidarity, gendered roles, and collective identity. The banjar system facilitates resource sharing and adaptive resilience amid modernization pressures by organizing collective work groups and preserving culinary knowledge. The study concludes that these rituals are essential for sustaining intangible cultural heritage. It recommends supportive documentation initiatives and culturally aware tourism policies that empower local women and recognize the banjar as a key institution for safeguarding this living tradition for future generations.